On the history and contents of the manuscript Vatican Ross. 350 (Minerva, 2018)
This paper concerns the history and contents of the manuscript Città del Vaticano, Biblioteca Apostolica Vaticana, Ross. 350 (15th century). A previously lost ex libris of the abbey in Florence has newly been found by using ultraviolet light. The paper also introduces the comparison to other manuscripts to allow the reconstruction of the full text. The diffusion of its contents, related to a codex in the Bibliothèque Nationale de France, lat. 2997, might point to a German origin. The manuscript transmits a hitherto unidentified text: an excerpt from Ephraim’s De compunctione cordis, a late-antique translation from Greek. The text suggests that the codex was commissioned by an unknown secular cleric who actively intervened on the text according to his own interests.
Keywords: Ross. 350; Abbey at Florence; Liber de compunctione cordis; Latin Ephraim